(untitled) (Research, Society and Development, 2024)
Mangroves play a vital role in the environment and coastal communities, acting as natural barriers against erosion and providing essential ecosystem services. On Cotijuba Island, the erosion process has been exacerbated by the removal of native vegetation, necessitating effective measures to halt the progression of degradation. This study aimed to evaluate the potential of Rhizophora mangle (red mangrove) propagules as a Nature-Based Solution (NBS) to mitigate erosion, restore degraded areas, and protect local livelihoods through a project implemented in two rural communities on the island. The project has been developed with the active involvement of residents, as part of a collective effort inspired by Citizen Science. Two groups of 35 participants collected and planted over one thousand propagules in critical areas within these communities. Regular monitoring revealed a 97% survival rate, attributed to the natural adaptation of the propagules, the mangroves’ resilience, and the nutrient-rich characteristics of the estuary. However, uneven plant growth was observed, highlighting the importance of using nurseries and improving monitoring indicators to maximize project success. The study concluded that the species’ potential for restoring degraded areas, this project promoted environmental education among participants. Nonetheless, the initiative’s future depends on continued support and funding to enhance monitoring, expand its scope, and replicate these solutions in other similarly threatened areas on the island.